Stanley in space - Brown, Jeff, 1926-2003 (HarperTrophy, 2003)
When the residents of a far-distant planet send a message to Earth asking for someone to meet with them, the President of the United States asks Stanley Lambchop, an all-American boy, to be his ambassador.